Assessment of the Energy Use for Water Supply in Beijing. (October 2018) - Liu, Jiahong; Wang, Dong; Xiang, Chenyao; Xia, Lin; Zhang, Kun; Shao, Weiwei; Luan, Qinghua
Abstract: Urban water supply systems consist of water intaking, water delivery, water purification, water distribution, and other processes that require energy. As urban population increases, water resources must be drained from a larger watershed and delivered through longer pipelines. Additionally, the requirements of water purification techniques are being raised, and higher building height poses challenges to water distribution. All these factors have caused evident changes in the energy use in the water supply system. Estimation of the energy used in the water supply system is one of the bases for low-carbon city construction and assessments. This paper provides a method for assessing the energy use by a water system in an urban area and performs a case study for Beijing, China. This study investigated the urban water supply system of Beijing from 1979 to 2017 by collecting data of water sources, water treatment techniques, delivery pipelines, water pressure, and seepage rates. It estimated the energy use per cubic unit of water in the water supply system and plotted the trend through time. The results showed that the energy use per cubic unit of water supply in Beijing increased from 0.30 KWh to 0.65 KWh from 1979 to 2014. After the commissioning of the South-to-North Water Diversion Project in 2014, the energy use per cubic unit water was altered structurally and remained steady, because the water transported by the project replaced groundwater and reduced the electricity requirement for pumping. The results demonstrate that the South-to-North Water Diversion Project significantly helps Beijing reduce carbon emissions.